Effect of curcumin on rheumatoid arthritis: a systematic review and meta-analysis - Kou, Haiyang; Huang, Lei; Jin, Meng; He, Qi; Zhang, Rui; Ma, Jianbing (Frontiers in Immunology, 2023)
Objective: The aim of this study is to evaluate the effectiveness and safety of curcumin in rheumatoid arthritis patients. Methods: A computerized search from PubMed, Embase, Cochrane Library, and Web of Science databases was performed until 3 March 2023. Literature screening, basic data extraction and risk of bias evaluation were independently performed by two researchers each. The quality evaluation of the literature was performed according to the Cochrane Handbook for Risk of Bias Assessment tool for treatment evaluation. Results: The current study includes six publications covering 539 rheumatoid arthritis patients. The activity of rheumatoid arthritis was assessed using erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), protein, disease activity score (DAS), rheumatoid factor (RF), Visual Analogue Scale (VAS) pain, tender joint count (TJC) and swollen joint count (SJC). ESR (MD = -29.47, 95% CI [-54.05, -4.88], Z=2.35, P = 0.02), DAS28 (MD = -1.20, 95% CI [-1.85, -0.55], Z=3.62, P = 0.0003), SJC (MD = -5.33, 95% CI [-9.90, -0.76], Z = 2.29, P = 0.02) and TJC (MD = -6.33, 95% CI [-10.86, -1.81], Z = 2.74, P = 0.006) showed significantly change in experimental patients compared with controls. Conclusion: Curcumin is beneficial for rheumatoid arthritis treatment. Inflammation levels and clinical symptoms in patients with rheumatoid arthritis can be improved by curcumin supplementation. Large sample randomized controlled trials on the effects of curcumin on patients with rheumatoid arthritis are needed in the future.